The Effect of Profitability, Liquidity, Size and GCG on the Value of Companies Moderated by Capital Structure - Fauziah, Layla; Widhiastuti, Susanti (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This research aims to explore the role of capital structure in moderating the effects of profitability, liquidity, company size, and good corporate governance on firm value. The study focuses on companies consistently listed in the LQ45 index on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Using a purposive sampling method, a total of 25 companies were selected as the sample. Secondary data for the study were obtained from the financial reports of these companies, available on the official website of the IDX. The analysis was carried out using the SEM-PLS method with the Warp-PLS 8.0 software at a 95% confidence level. The results reveal that profitability and liquidity have a significant effect on firm value, while company size and good corporate governance show no significant influence. Furthermore, the capital structure positively and significantly moderates the relationship between profitability and good corporate governance with firm value but does not moderate the effects of liquidity and company size on firm value.